2007
DOI: 10.3732/ajb.94.9.1470
|View full text |Cite
|
Sign up to set email alerts
|

Impact of global warming on a group of related species and their hybrids: cherry tree (Rosaceae) flowering at Mt. Takao, Japan

Abstract: Climate change is affecting plant phenology worldwide. Phenological responses vary among species, but it is not clear how responses differ among closely related species. We examined a 25-yr record (1981-2005) of flowering times for 97 trees, representing 17 species and hybrids of cherry (Cerasus sp. or Prunus sp.) grown at Mt. Takao, in Tokyo, Japan. The cherry trees flowered earlier over time, by an average of 5.5 d over the 25-yr study. Earlier flowering was explained largely by a 1.8°C increase in February-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 43 publications
9
87
2
2
Order By: Relevance
“…This result indicated that the period influenced the trend estimate of phenophases, which was also suggested by other studies [12,19,29]. Although no significant trends were found, FFD of three ornamental plants still had a strong interannual variance with a standard deviation of 6.3 to 7.9 days, which was in accordance with FFD time series observed in other parts of the world [12,[30][31][32]. Such a high variability in the flowering date further hampers the detection of trends in flowering phenology.…”
Section: Discussionsupporting
confidence: 85%
“…This result indicated that the period influenced the trend estimate of phenophases, which was also suggested by other studies [12,19,29]. Although no significant trends were found, FFD of three ornamental plants still had a strong interannual variance with a standard deviation of 6.3 to 7.9 days, which was in accordance with FFD time series observed in other parts of the world [12,[30][31][32]. Such a high variability in the flowering date further hampers the detection of trends in flowering phenology.…”
Section: Discussionsupporting
confidence: 85%
“…degree-days) often predicts well the date of flowering in plants (e.g. Jackson 1966;Diekmann 1996), and flowering phenology commonly tracks interannual variation in air temperatures (Fitter et al 1995;Sparks et al 2000;Miller-Rushing et al 2007). Heat accumulation similarly affects development rate and, hence, the timing of appearance of adults, in many economically important insect species (Embree 1970;Kemp & Onsager 1986;Régnière et al 2007).…”
Section: (B) Photoperiodmentioning
confidence: 99%
“…However, temperature also has a strong effect on development rate, and interacts with the photoperiod response to determine the actual timing of flowering (Billings andMooney 1968, Wilczek et al 2010). Studies using long-term data on flowering phenology in temperate-zone plants frequently emphasize the temperature effect, showing good correlations between springtime temperatures and dates of first or peak flowering (e.g., Fitter et al 1995, Miller-Rushing et al 2007, Miller-Rushing and Primack 2008.…”
Section: Determinants Of Flowering Phenologymentioning
confidence: 99%